Interculturalidad y Lecto–-Escritura en Estudiantes de Segundo Año de Educación General Básica en la Escuela “Corazón de Jesús” Riobamba, San Luis - Ruiz Ruiz, Leonor Rocío (2020)
The learning difficulties for reading and writing in basic general education centers and especially in rural areas have not allowed students to learn this complex process in an efficient way since the existing texts are not adapted to their realities, to their culture and to learn in a playful way; in this sense, the purpose of this research is the design and application of a pedagogical guide with an intercultural approach through the development of dynamic activities that promote respect for cultural diversity and the strengthening of the reading and writing skills in the students of the Second Year of Basic Education of the “Corazón de Jesús” Educational Unit, located in the San Luis parish belonging to the Riobamba canton. The methodology is qualitative and quantitative, techniques such as interviews aimed to the directing and teaching staff were used in order to make the diagnosis based on the variables of inter culturality and reading – writing skills, and the need to carry out new strategies in reality became evident in order to promote inter culturality and strengthening the reading and writing process. Prior to the design and application of the pedagogical guide, a first record of the students’ level of knowledge and skills (pre-test) was requested, supported by an observation sheets based on inter culturality and reading-writing criteria, respectively, from which the design and application of activities contained in this guide started, after its application, a second record was created (post-test) in which a great advance in the development of skills and knowledge with respect to the previously specific variables was found. In this way and with the data obtained, a general assessment was carried out using the Likert scale in which the tension of the proposed pedagogical guide is reflected. The validity of the proposal was carried out by four expert professors in the area, they agreed on its validity and applicability. Finally, preventive recommendations were established, they will facilitate a better applicability of activities.